TOTAL CHROMATIC NUMBER OF SPLIT GRAPHS - Hung, Le Xuan (Acta Scientiae et Intellectus, 2024)
A graph G (V,E) is called a split graph if there exists a partition V I K such that the subgraphs of G induced by I and K are empty and complete, recpectively. We will denote such a graph by S(I K,E) . The notion of split graphs was introduced in 1977 by S. Foldes and P.L. Hammer. These graphs have been paid atthention also because they have connection with packing and knapsack problems, with the matroid theory, with Boolean function. In this paper, some sufficient conditions for split graphs with